Effect of Photo-Bio modulation on lipid profile in Patients with type 2 diabetes mellitus: A Randomized Clinical Trial - Hany Mahmoud Fares; Hend Abd El-Moneam Abd El-Moneam; Asmaa Abdel Maksoud Ghanem; Basant Hamdy Elrefaey; Tamer I. Abo Elyazed (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Objective: to investigate the low level laser therapy (LLLT) efficiency by using laser watch as an adjunctive therapy of dyslipidemia in type 2 diabetes mellitus (T2DM) patients. Methods: The study included sixty adult patients with diabetic dyslipidemia of both gender. They were split into two groups. Study group received anti diabetic drugs along with laser watch therapy (3 sessions /week for 12 weeks), while control group received only anti diabetic drugs. Blood sugar (FBS, 2HPP and HbA1C) and lipid panel (TG, TC, LDL and HDL) were measured before and at completion of the study. Results: A significant improvement in blood sugar and serum lipid profile was seen in both groups (P < 0.001), the study group, however, displayed more significant outcomes (P < 0.001). Conclusion: LLLT using laser watch can be used as a complementary treatment for dyslipidemia in T2DM patients to improve blood lipid profile and blood sugar